The economic consequences of a Tobin tax: An experimental analysis - Michael Hanke; Jürgen Huber; Michael Kirchler; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2007)
The effects of a Tobin tax on foreign exchange markets have long been disputed. We present an experiment with currency trading on two markets, where either none, one, or both markets are taxed. Our results confirm the hitherto undisputed issues: a tax reduces trading volume, shifts market share to untaxed markets, and leads to negligible tax revenues if tax havens exist. Concerning the controversial issues we find that (i) volatility effects depend on the existence of tax havens and on market size, (ii) market efficiency remains unaffected by the tax, (iii) short-term speculation is reduced, and (iv) the tax has persistent effects even after its abolishment.
Keywords: C91; E62; 330; Tobin tax; experiment; foreign exchange; market efficiency; trading volume; volatility; Tobinsteuer; Markteffizienz; Börsenumsatz; Volatilität; Devisenmarkt; Schätzung; Test